2009
DOI: 10.1007/s10567-009-0040-9
|View full text |Cite
|
Sign up to set email alerts
|

Youth Exposed to Violence: Stability, Co-occurrence, and Context

Abstract: With considerable literature establishing how separate types of violence disrupt the lives of children, there is emerging interest in examining violence across multiple interpersonal domains. This paper examines four commonly occurring and frequently researched domains of violence exposure: marital physical aggression, mother-to-youth aggression, father-to-youth aggression, and community violence. A community-based sample of 103 parents and youth provided three waves of data at annual intervals beginning when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 66 publications
4
67
0
3
Order By: Relevance
“…The presence of IPV in the family increases the risk that children will in turn be the direct victims of maltreatment [29][30][31][32][33][34]. Several studies have shown that exposure to both IPV and direct CM has an even more deleterious effect on children's adaptation [16,17,35,36].…”
Section: Consequences For Children Of Being Exposed To Intimate Partnmentioning
confidence: 99%
“…The presence of IPV in the family increases the risk that children will in turn be the direct victims of maltreatment [29][30][31][32][33][34]. Several studies have shown that exposure to both IPV and direct CM has an even more deleterious effect on children's adaptation [16,17,35,36].…”
Section: Consequences For Children Of Being Exposed To Intimate Partnmentioning
confidence: 99%
“…Toutefois, les rapports de pouvoir ne caractérisent pas tous les types de violence au sein de la famille, certains pouvant découler davantage du stress ou des conditions de vie difficiles auxquels sont confrontés les parents (Sprang et al, 2005 ;Stith et al, 2011) ou l'aidant naturel dans le cas des personnes âgées (Roberto et al, 2013). Le fait d'étudier les liens entre les violences conjugales et d'autres formes de violence familiale permet de prendre en considération les nombreuses situations où les violences se présentent de manière concomitante au sein d'une même famille (Chang et al, 2011 ;Finkelhor et al, 2011 ;Goddard et Bedi, 2010 ;Clément et al, 2013 ;Margolin et al, 2009). Ces violences concernent tous les membres de la famille : les femmes, les hommes et les enfants exposés à la violence conjugale.…”
Section: En Quoi Les Connaissances Sur Les Violences Familiales Et Stunclassified
“…Although numerous studies have documented an association between violence experiences and alcohol use among adults, limited research has investigated the association between interpersonal violence experiences and alcohol use among adolescents. In the general population of adolescents, studies have examined interpersonal violence experiences or childhood maltreatment and various mental health outcomes (for example, Boney-McCoy & Finkelhor, 1995, 1996Margolin et al, 2009;Stein et al, 2003;Voisin, 2007). However, limited research exists on the link between interpersonal violence experiences and alcohol use outcomes in this population (Giaconia et al, 2000;Hamburger et al, 2008;Kilpatrick et al, 2000Kilpatrick et al, , 2003.…”
Section: Interpersonal Violence and Alcohol Usementioning
confidence: 99%
“…In the general population, studies have found that adolescents who have experienced community violence and traumatic events exhibit more psychological and behavioral symptoms than adolescents who have not experienced such events (Aisenberg & Herrenkohl, 2008;Boney-McCoy & Finkelhor, 1995, 1996Margolin et al, 2009;Reijneveld, Crone, Verhulst, & Verloove-Vanhorick, 2003;Stein et al, 2003). Despite the high prevalence of alcohol use among adolescents, we know of only four studies that have explored associations between alcohol use and violence experiences in the general population of adolescents (Giaconia et al, 2000;Hamburger, Leeb, & Swahn, 2008;Kilpatrick et al, 2000Kilpatrick et al, , 2003.…”
mentioning
confidence: 99%